2011
DOI: 10.1103/physrevb.84.115110
|View full text |Cite
|
Sign up to set email alerts
|

Quantum criticality in Ce2PdIn8: A thermoelectric study

Abstract: We report the Nernst effect (ν) and thermoelectric power (S) data for the Ce2PdIn8 heavyfermion compound. Both S and ν behave anomalously at low temperatures: the thermopower shows a Kondo-like maximum at T = 37 K, while the Nernst coefficient becomes greatly enhanced and field dependent below T ≈ 30 K. In the zero-T limit S/T and ν/T diverge logarithmically, what is related to occurrence of the quantum critical point (QCP). Presented results suggest that the antiferromagnetic spin-density-wave scenario may be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…Most intriguingly, it has also been suggested that Ce 2 PdIn 8 may fulfill the necessary conditions for the formation of a unique modulated Fulde-Ferrell-Larkin-Ovchinnikov superconducting state [6], which possible occurrence at the magnetic highfield-low-temperature corner of the H − T phase diagram of CeCoIn 5 is presently being hotly debated [11]. The many common features between CeCoIn 5 and Ce 2 PdIn 8 motivate further comprehensive studies of the physical behavior in the latter compound.In this Communication we report on the Hall effect and the transverse magnetoresistivity of Ce 2 PdIn 8 , which both appeared highly anomalous yet consistent with the quantum criticality scenario, previously evoked based on the electrical resistivity [5,6,8], thermoelectric [12] and heat capacity [4,9] data. The polycrystalline sample used in the present study was previously characterized by means of X-ray diffraction, magnetic susceptibility, electrical resistivity and heat capacity measurements [5].…”
supporting
confidence: 86%
See 2 more Smart Citations
“…Most intriguingly, it has also been suggested that Ce 2 PdIn 8 may fulfill the necessary conditions for the formation of a unique modulated Fulde-Ferrell-Larkin-Ovchinnikov superconducting state [6], which possible occurrence at the magnetic highfield-low-temperature corner of the H − T phase diagram of CeCoIn 5 is presently being hotly debated [11]. The many common features between CeCoIn 5 and Ce 2 PdIn 8 motivate further comprehensive studies of the physical behavior in the latter compound.In this Communication we report on the Hall effect and the transverse magnetoresistivity of Ce 2 PdIn 8 , which both appeared highly anomalous yet consistent with the quantum criticality scenario, previously evoked based on the electrical resistivity [5,6,8], thermoelectric [12] and heat capacity [4,9] data. The polycrystalline sample used in the present study was previously characterized by means of X-ray diffraction, magnetic susceptibility, electrical resistivity and heat capacity measurements [5].…”
supporting
confidence: 86%
“…In this Communication we report on the Hall effect and the transverse magnetoresistivity of Ce 2 PdIn 8 , which both appeared highly anomalous yet consistent with the quantum criticality scenario, previously evoked based on the electrical resistivity [5,6,8], thermoelectric [12] and heat capacity [4,9] data. The polycrystalline sample used in the present study was previously characterized by means of X-ray diffraction, magnetic susceptibility, electrical resistivity and heat capacity measurements [5].…”
supporting
confidence: 86%
See 1 more Smart Citation
“…The most studied member of this series is the n = 1 member CeCoIn 5 (T c = 2.3 K) (16), in which clear evidence for non-FL behaviors in the normal state (17,18) and nodal superconductivity has been found (6,19,20). The recent discovery of superconductivity at ambient pressure in the n = 2 member Ce 2 PdIn 8 (T c = 0.68 K) (21), which exhibits very similar non-FL properties (22)(23)(24)(25)(26)(27) to those in CeCoIn 5 , allows a detailed comparison of the superconducting properties to extract common features in these superconductors near the antiferromagnetic QCP.…”
Section: Resultsmentioning
confidence: 99%
“…Non-Fermi-liquid behavior was observed in both macroscopic [6][7][8][9][10] and microscopic [11,12] measurements at low temperature, implying that Ce 2 PdIn 8 is located very close to a QCP. It was further suggested that a twodimensional (2D) SDW-type QCP is induced by magnetic field near the upper critical field, H c2 ≈ 2 T [9].…”
mentioning
confidence: 90%